1997
DOI: 10.1016/s0014-5793(97)00329-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses, not promoter inactivation, are responsible for decreased long‐term expression following plasmid gene transfer into skeletal muscle

Abstract: Long-term high-level in vivo gene expression appears to depend on the promoter chosen to drive the gene of choice. In many cases the promoter appears to 'switch off some time after in vivo gene transfer. We demonstrate that, following intramuscular injection of ß-galactosidase reporter plasmids, promoter 'switch off is due to elimination of fibres expressing the transferred reporter gene by activation of a Thl (cytotoxic) immune response. This finding, in the absence of stimulation of the immune system by vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 24 publications
3
44
1
Order By: Relevance
“…Intramuscular injection of plasmid encoding ␤-galactosidase generated a similar cytotoxic response that led to destruction of transfected muscle fibres in normal but not in nude Balb/c mice. 30 A decline in the number of fibres in the mdx compared with nude mdx was also observed when the muscle-specific skeletal actin (HSA) promoter was used to drive expression of minidystrophin. However, the drop in dystrophin-positive fibres was not as dramatic as the results in animals treated with the CMV-driven minidystrophin plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intramuscular injection of plasmid encoding ␤-galactosidase generated a similar cytotoxic response that led to destruction of transfected muscle fibres in normal but not in nude Balb/c mice. 30 A decline in the number of fibres in the mdx compared with nude mdx was also observed when the muscle-specific skeletal actin (HSA) promoter was used to drive expression of minidystrophin. However, the drop in dystrophin-positive fibres was not as dramatic as the results in animals treated with the CMV-driven minidystrophin plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…All injections (25 l) were carried out using a 27-gauge needle in a proximal to distal direction inside the anterior tibial muscle, under fentanyl/fluanisone and midazolam general anaesthesia (respectively, Hypnorm; Janssen Pharmaceutical, High Wycombe, UK and Hypnovel; Roche, Welwyn Garden City, UK) as previously described. 30 Three injections of plasmid were performed on the same muscle with intervals of 1 week between injections. Samples were then collected 2 to 10 weeks after the last injection.…”
Section: Intramuscular Injection Of Plasmid Dnamentioning
confidence: 99%
“…2 As reported by us and others, immune responses triggered by gene transfer depend on both the transgene and the nature of the vector. 42,43 In the case of intramuscular administration of plasmid DNA, the fate of transgene expression seems often to be linked to an immune response directed towards the transgene itself rather towards the vector, 44 as suggested by data on persistence of the vector DNA or mRNAs in the injected muscles. 24,45 Various studies reported an anti-dystrophin immune response following intramuscular injections of vectors, especially viruses.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is clear that loss of the therapeutic gene expression and transfected cells is immune mediated, since such losses do not occur in immunocompromised animals. [4][5][6] The knowledge gathered from the field of DNA-based immunization may provide important insight for the field of gene therapy. It was initially thought that the efficacy of DNA vaccines was by virtue of in vivo synthesis of antigen in transfected cells, for example muscle cells after intramuscular (i.m.)…”
Section: Introductionmentioning
confidence: 99%